PELATIHAN UPGRADING SOFTSKILL MOTOR BAKAR INJEKSI UNTUK SISWA SMK KELAS 12 DI SMK NEGERI 1 NISAM DI DESA TINGKEUM, NISAM, ACEH UTARA - Teuku Hafli; Nurul Islami; Reza Putra; A Asnawi; M. H. Rais; P. A. Pane (Yayasan Hurriah, Banda Aceh, 2022)
The Unimal Community Partnership Program (PKM) has carried out community service by cooperating with SMK N.1 Nisam as a partner to train and upgrade the soft skills of teachers and students with injection fuel motor type machines available in the Lab. Unimal Mechanical Engineering Study Program. This service program is also a promotional event for the Mechanical Engineering Study Program to be able to increase the number of students joining the study program. The target output of this PKM is the ability of students to understand the differences in fuel motors in general and have special skills if they want to be entrepreneurs in vehicle workshops. By being able to classify problems arising from the injection motor system through software, error codes and flashing indications, this system has been adopted in all motorized vehicles both two-wheeled and four-wheeled. The free motorcycle training and service, which is a practical event for students, has increased the enthusiasm and skill of final year students at SMKN 1 Nisam